2009
DOI: 10.1021/la903381f
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Improve Poly(3-hexyl thiophene) (P3HT) Crystalline Behavior: Decreasing Chains Entanglement To Promote Order−Disorder Transformation in Solution

Abstract: We promoted order-disorder transformation of poly(3-hexylthiophene) (P3HT) in solution by ultrasonic oscillation which substantially improved crystallinity in its pure film. P3HT with low molecular weight (M(w)) dispersed very well in p-xylene solvent and few aggregates generated in the solution. For P3HT with high M(w), the results suggested the coexistence of two phases: disordered coils in solution and ordered microcrystals in suspension. Upon ultrasonic oscillating, more ordered precursors generated in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 42 publications
11
148
0
Order By: Relevance
“…Thus, the importance of heating solutions before the next processing step [68,144,145] for the promotion of single coil chains is proved. Apart from thermal energy, ultrasonic vibration is also a effective method for disentanglement as reported by Zhao et al (Figure 18I) [146,147]. They reported that the P3HT chains with a larger molecular weight had a more severe entanglement due to the binary-hooking contact prevailing arising from the folding and distortion of conformation of high-M W polymer.…”
Section: Disentanglementmentioning
confidence: 91%
“…Thus, the importance of heating solutions before the next processing step [68,144,145] for the promotion of single coil chains is proved. Apart from thermal energy, ultrasonic vibration is also a effective method for disentanglement as reported by Zhao et al (Figure 18I) [146,147]. They reported that the P3HT chains with a larger molecular weight had a more severe entanglement due to the binary-hooking contact prevailing arising from the folding and distortion of conformation of high-M W polymer.…”
Section: Disentanglementmentioning
confidence: 91%
“…[5][6][7][8][9][10] A number of recent studies have demonstrated that molecular ordering along the polymer backbone and between chains is far more important to carrier transport in high molecular weight (Mw) polymer films than domain boundaries. [11][12][13][14][15][16] However, high Mw semi-flexible polymers are thought to be difficult to push into a highly molecularly ordered state due to entanglements and interactions which can inhibit molecular diffusion and challenge conformational transitions. 11,13,17 Polymer crystallization improves the molecular stacking order and planarization of the backbone in the solid state, hence there have been a number of reports linking crystalline order to carrier transport.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,17 Polymer crystallization improves the molecular stacking order and planarization of the backbone in the solid state, hence there have been a number of reports linking crystalline order to carrier transport. 7,18,19 Along this line, several strategies have been pursued to control molecular self-assembly and thin film microstructure, including by decreasing chain entanglements in the solution state, 12,13,17 tuning solution-processing conditions, [20][21][22][23][24] surface functionalization with a self-assembled monolayer (SAM) [25][26][27] and applying post-deposition thermal/solvent vapour annealing. [28][29][30] 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28] The rod conformation enhances the crystallization via the faceto-face assembly of the p-conjugation. [22,23] The increased conjugation length brings a red shift in UV-Visible absorption, [21][22][23][24] changing the color of the solution from orange to deep purple, as shown in the inset camera images. The P3HT solution was in a liquid nitrogen bath until the solution temperature was decreased to À40 8C and it was taken out in air.…”
Section: à2mentioning
confidence: 99%